2021
DOI: 10.1159/000512585
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment with Belimumab in a Patient with Refractory Systemic Lupus Erythematosus after Initiation of Hemodialysis: Considering the Synergistic Effect of Belimumab and Immunological Burn-Out Phenomenon in End-Stage Renal Disease Patients on Hemodialysis

Abstract: <b><i>Background:</i></b> In patients with systemic lupus erythematosus (SLE), disease activity can persist even after initiating dialysis. However, guidelines for the treatment of patients with SLE after dialysis is initiated have not yet been established. <b><i>Case Presentation:</i></b> We describe the case of a 54-year-old Japanese woman who was diagnosed with SLE at age 12, progressed to end-stage renal disease (ESRD), and initiated hemodialysis for lupus ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…However, the patient developed Pneumocystis carinii pneumonia and congestive heart failure after 3 weeks, and the dose of Belimumab was reduced from 10 mg/kg to 4 mg/kg after the patient’s condition improved due to concerns about the risk of reinfection. After 7 doses of Belimumab, the SLEDAI score decreased to 4, and the only reported AE was pneumonia ( 19 ). An Italian patient with SLE on peritoneal dialysis for ESRD was treated with Belimumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the patient developed Pneumocystis carinii pneumonia and congestive heart failure after 3 weeks, and the dose of Belimumab was reduced from 10 mg/kg to 4 mg/kg after the patient’s condition improved due to concerns about the risk of reinfection. After 7 doses of Belimumab, the SLEDAI score decreased to 4, and the only reported AE was pneumonia ( 19 ). An Italian patient with SLE on peritoneal dialysis for ESRD was treated with Belimumab.…”
Section: Discussionmentioning
confidence: 99%
“…The cases above shows that despite having entered maintenance dialysis, Belimumab is still an excellent treatment option for extrarenal lupus activity in SLE patients. However, special care should be paid to preventing infection during use, as Belimumab and uremia synergistically inhibit B cell lineage through different pathways ( 19 ). While all four of our cases had massive proteinuria and hypoalbuminemia at the onset, they also had concomitant acute kidney injury and decreased urine output.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Previously, Kazunori Karasawa and Valentina Binda reported that belimumab could alleviate immunologic flare in patients diagnosed as SLE, who were on maintenance dialysis (including hemodialysis and peritoneal dialysis). 17,19 In our study, Patient 7 was on maintenance dialysis for over 13 years. Even without obvious clinical manifestation, belimumab was applied in order to decrease the serological parameters.…”
Section: Discussionmentioning
confidence: 91%
“…Only two case report documented belimumab use in improving disease activity in SLE patients with maintenance dialysis and disease flare. 17,18 Therefore, we retrospectively review SLE patients combined with severe LN requiring RRT, who obtained belimumab therapy, in order to investigate the efficacy and safety issue of belimumab in patients receiving dialysis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of BLM on treating SLE after dialysis has not been previously investigated, at least to the best of our knowledge. The case report study by Karasawa et al (47) demonstrated that SLE activity was attenuated in a patient with SLE treated with BLM following hemodialysis. Another case study on a patient with SLE who was treated with BLM during peritoneal dialysis revealed that the clinical symptoms were significantly improved (48).…”
Section: Discussionmentioning
confidence: 98%